Post-pandemic e-teaching: Developing the Game for Microscopic Atom Simulation (GEMAS) to enhance students' scientific conceptions of phase structures - Zahran, Muhammad; Samsudin, Achmad; Novia, Hera; Fratiwi, Nuzulira Janeusse; Nurdini, Nurdini; Ningsih, Dena Tresna; Nugraha, Eki; Nasbey, Hadi; Sözbilir, Mustafa (Journal of Environment and Sustainability Education, 2025)
This research focuses on the early development of GEMAS (Game for Microscopic Atom Simulation) as an innovative digital teaching tool designed to support instruction on phase structures in physics education. In response to the post-pandemic shift towards technology-enhanced teaching, GEMAS was developed to integrate interactive, simulation-based pedagogy that enhances conceptual visualization. The study follows the 3D model (Define, Design, and Develop) and employs Multifaceted Rasch Measurement (MRFM) for evaluation. Validation was conducted by five experts, assessing curriculum alignment, scientific accuracy, language clarity, visual arrangement, and instructional effectiveness. These dimensions align with best practices in e-teaching, ensuring accessibility, engagement, and pedagogical rigor. MRFM analysis confirms the tool’s validity, with positive average scores across all indicators. The findings suggest that GEMAS is a well-designed digital resource, ready for implementation to enhance physics instruction in post-pandemic educational settings. The implications of this study extend beyond validating GEMAS as a tool; it demonstrates how immersive 3D simulations can address persistent misconceptions in physics education, particularly in post-pandemic contexts where digital engagement is critical. By bridging abstract concepts with interactive visualization, GEMAS offers a scalable model for enhancing e-teaching practices and fostering deeper conceptual understanding among students.